Implementation Of Criminal Enforcement In The Circulation Of VCD (Video Compact Disc) On The Level Of Investigations In Rembang Polres Area - Priyantono Priyantono; Jawade Hafidz (Jurnal Daulat Hukum, 2020)
This study aims to determine and analyze the implementation of criminal law enforcement in pirated VCD (Video Compact Disc) cases at the investigation level in the Rembang Police area, obstacles and efforts to overcome them.The method used is sociological juridical, descriptive analytical research specifications. The data used are primary data and secondary data. Data collection methods are field studies and library studies. The method of data analysis uses qualitative analysis. As a knife of analysis, law enforcement theory is used, and law effectiveness theory is used.The results showed that the implementation of criminal law enforcement in the case of pirated VCD (Video Compact Disc) at the level of investigation in the Rembang Police District area was in accordance with the provisions of the applicable laws and regulations, namely through several stages namely investigation, forced effort, examination, determination of suspects , filing, submitting case files to the public prosecutor and submitting the suspect and evidence to the public prosecutor. Obstacles in the implementation of criminal law enforcement in pirated VCD (Video Compact Disc) cases at the investigation level in the Rembang Police Precinct are investigators who have difficulty tracking down perpetrators, difficulties in bringing in expert witnesses, lack of legal awareness from perpetrators or from the public.Keywords: Criminal Law Enforcement; Investigation; Distribution Of Pirated Video Compact Discs.